Simulation as a decision support tool in maintenance float systems – the automatic generation of simulation programs - Peito, Francisco (2013)
This paper is concerned with the use of simulation as a decision support tool in maintenance systems, specifically in MFS (Maintenance Float Systems). For this purpose and due to its high complexity, in this paper the authors propose a flexible way to develop typical MFS models, for any number of machines in the workstation, spare machines and maintenance crews. Arena® simulation language is used to understand a specific MFS, create the corresponding MFS model and analyze most common performance measures.